The incidence and characteristics of purposeful heading in male and female youth football (soccer) within Australia - Peek, K.; Vella, T.; Meyer, T.; Beaudouin, F.; McKaya, M. (Journal of Science and Medicine in Sport, 2021)
Objectives: To quantify the incidence and characteristics of purposeful headers and unintentional head impacts during male and female youth football (soccer) games in Australia. Design: Cross-sectional observational study. Methods: Ten match-videos (total n = 110) per playing age (under 13-20 males; under 13-17 females) from the 2019 National Premier League season were coded for purposeful headers and unintentional head impacts. Total headers and head impacts as well as incidence rate (IR) per 1000 match-hours for different match characteristics were calculated. Results: Purposeful headers accounted for 99% (n = 4615, IR:1618) of total head impacts. The IR of purposeful headers per 1000 match-hours was highest for under-15 males (IR:2117) and under-17 females (IR:2090) followed by under-20 males (IR:1761). Midfielders completed the most headers in all female age groups (mean IR:713) and under 13-14 males (mean IR:891), with defenders completing the most headers in under 15-20 males (mean IR:760). Heading duels accounted for 16% of total headers with most headers performed during free play (68%), throw-ins (15%), free kicks (12%) and corner kicks (5%). Only 57 head impacts (IR:20) were coded as unintentional head impacts resulting from being struck by the ball or opponent body part with 4 (IR:1.4) requiring medical attention. Conclusions: Heading is a complex skill. Given the propensity of youth players of all ages to purposefully head the ball, consideration should be given to coaching heading technique based on specific game scenarios for their playing position and age group. The findings of this study can be used to inform heading guidelines.